Schools of public health as a cornerstone for pandemic preparedness and response: the Africa COVID-19 experience - Rawlance Ndejjo; Honore Kabwebwe Mitonga; Woldekidan Amde; Grace Biyinzika Lubega; Adamson S. Muula; Damen Haile Mariam; Steven N. Kabwama; Sean Mark Patrick; Desderius Haufiku; Maryam Amour; Marc Bosonkie; Trasias Mukama; et al. (BMC, 2024)
Abstract Background The Coronavirus disease (COVID-19) pandemic caused significant morbidity and mortality in Africa, in addition to other socio-economic consequences. Across the continent, Schools of Public Health (SPHs) played several roles in supporting national, regional, and global response to the pandemic. Following a published and grey literature search, this paper reviews and analyses the contribution of SPHs in Africa during the COVID-19 pandemic. Contribution of the Schools of Public Health SPH faculty in most countries contributed their expertise through COVID-19 task forces and advisory committees where they guided and supported decision-making. Faculty also supported the identification, review, and synthesis of rapidly evolving global and local evidence, adapting it to the local context to guide policy decisions. Through research, SPHs contributed to a better understanding of the disease epidemiology, response interventions, as well as prevention and control measures. SPHs engaged in training field epidemiologists, frontline health workers, and district response teams. SPH staff, students and field epidemiology trainees also supported field activities including surveillance, contact tracing, as well as managing quarantine facilities and points of entry. SPHs engaged in public education and awareness-raising initiatives to share information and dispel misinformation. In partnership with other stakeholders, SPHs also developed important innovations and technologies. Conclusion SPHs are a critical pillar for pandemic prevention, preparedness, and response, that support health systems with important functions. To further enhance their capacity, efforts to improve coordination of SPHs, strengthen collaboration among schools, harmonize training and curricula, and enhance capacity for advanced research are needed. There is also a need to bridge the inequities in capacity and resources that exist among SPHs across regions and countries.